Pengaruh Rasio Keuangan Terhadap Nilai Perusahaan Pada Perusahaan Sektor Infrastruktur Utilitas Dan Transportasi Periode 2017-2019 - Rizkika Astari; Hartini (Journal of Management and Business, 2021)
The purpose of this study was to determine the effect of the liquidity ratio (current ratio), solvency ratio (debt to equity ratio) and the ratio of profitability (return on equity) to firm value (price earning ratio).The sample in this study were 15 infrastructure, utility and transportation companies listed on the BEI. This study used panel data regression analysis with data collection using the documentation method in the form of data from financial statements. The data obtained is processed using panel data regression analysis techniques through software eviews 9.The results of this study are (a) the current ratio has a significant effect on the price earning ratio (b) the return on equity has a significant effect on the price earning ratio, and (c) the debt to equity ratio has an effect but not significant on the price earning ratio.